Turnover Intention pada Karyawan Generasi Z di Industri Ritel Jabodetabek: Peran Burnout dan Work-Life Balance - Nurbaiti Junita Ardiani; Pundani Eki Pratiwi (Universitas Muhammadiyah Metro, 2026)
High employee turnover rates in the retail industry present a significant challenge to company sustainability, particularly as Generation Z continues to become a more dominant workforce. The retail industry is important to study because it is characterized by a fast-paced, dynamic work environment that demands a high level of responsiveness to customer needs, often resulting in employees facing ongoing work pressure. The uniqueness of retail employee work behavior lies in the need to remain responsive and provide optimal service within a busy and often unpredictable work schedule. This situation has the potential to lead to excessive workload, physical and emotional exhaustion known as burnout, and difficulty balancing work and personal life. This study examines the impact of burnout and work-life balance on turnover intention among Generation Z employees in the Jabodetabek retail sector. It adopts a quantitative approach, utilizing a survey method and a correlational design. The population includes Generation Z retail workers in Jabodetabek, selected through purposive sampling. Data were gathered online via questionnaires and involved 185 respondents fitting the criteria. Analysis employed Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Results indicated that burnout had a positively impacts turnover intention, while work-life balance negatively influences. Both burnout and work-life balance were proven to be significant predictors of turnover intention among Generation Z employees in the retail industry. The findings of this study have implications for retail companies to focus more on workload management and work-life balance policies in order to reduce turnover intention levels, as well as contribute to the development of industrial and organizational psychology studies related to the work characteristics of Generation Z.